The French Mussel Watch: More than two decades of chemical contamination survey in Mediterranean coastal waters. (June 2023) - Briand, Marine J.; Herlory, Olivier; Briant, Nicolas; Brach-Papa, Christophe; Boissery, Pierre; Bouchoucha, Marc
Abstract: Active biomonitoring of chemical contamination ( e.g., Cd, Hg, Pb, DDT, PCB, PAH) in French Mediterranean coastal waters has been performed for more than two decades. This study aimed at presenting the current contamination in 2021 and the temporal evolution of concentrations from 2000. Based on a relative spatial comparison, low concentrations were measured in 2021 at most sites (>83 %). Also, several stations with moderate to high levels were highlighted in the vicinity of major urban industrial centers ( e.g., Marseille, Toulon) and near river mouths ( e.g., Rhône, Var). Over the last 20 years, no major trend was revealed, mostly, especially for the relative high-level sites. This likely constant contamination over time, plus slight increases of metallic elements at a few sites, still raise questions on the efforts that remain to be made. The decreasing trends of organic compounds, in particular PAH, provide evidence of the efficiency of some management actions. Highlights: Contamination in mussels from French waters has been monitored over two decades. In 2021, most sites showed relative low concentrations. Most contaminants revealed constant levels over the last 20 years at most stations. Sites near urban industrial centers or river mouths remain contamination hotspots. PAH revealed clear decreasing trends for 63 % of stations.